A Comparative Study on the Shaping Ability of K3, Profile and ProTaper Instruments in Simulated Curved Root Canals - Suneelkumar, Chinni; Savarimalai Karumaran, Chellaswamy; Ramachandran, Sundararaman; Indira, Rajamani; Shankar, Padmabhan; Kumar, Anil (Iranian Endodontic Journal, 2010)
INTRODUCTION: The objective of this study was to compare the shaping ability of three rotary filing systems; constant taper K3 instruments, constant taper ProFile instruments and progressive taper ProTaper rotary instruments in clear resin blocks with simulated curved root canals. MATERIALS AND METHODS: Forty five resin blocks were divided into three groups. Group A preparation was conducted with K3, Group B with ProFile and Group C with ProTaper instruments. Pre and post instrumentation images were superimposed and assessment of the canal shape was completed with a computer image analysis program at 14 levels of the root canal system. RESULTS: Group A inner and outer curvature pre and post instrumentation values were significantly different (P<0.05) at levels 3; at level 13 only the outer curvature and levels 6, 7, 8 the inner curvature had significantly different values between pre and post instrumentation. Group C had significant P values (P<0.05) at levels 2, 3, 4, 12, 13 in the outer curvature and at levels 6, 7, 8 of the inner curvature. CONCLUSION: Overall, all three rotary instruments maintained root canal curvatures well. ProTaper instruments significantly removed more resin material from outer canal curvature in the apical third when compared to the other two groups.